Managing Employee Performance: From Leadership to Readiness for Change - Asbari, Masduki; Dylmoon Hidayat, Dylmoon; PURWANTO, AGUS (International Journal of Social and Management Studies, 2021)
This study aimed to measure the effect of transformational leadership and readiness for change on employee performance of the employee of a chemical industry. In this study, readiness for change is mediating variable. Data was collected from 220 returned questionnaire of samples taken by random sampling. Data was analysed using SEM method with SmartPLS 3.0 software. The results of this study showed that transformational leadership had a significant effect on readiness for change, transformational leadership and readiness for change have a significant effect on the employee performance, readiness for change have a positive and significant effect on the relationship between transformational leadership and employee performance. Readiness for change functioned as a partial mediator. This new research proposed a model for managing employee performance among the employee of the chemical industry in Indonesia through developing transformational leadership practice with readiness for change as a mediator. This research could pave the way to improve employee readiness in facing the era of industrial revolution 4.0.